Product flow analysis using trade statistics and consumer survey data: a case study of mobile phones in Australia. (1st October 2016) - Golev, Artem; Werner, Tim T.; Zhu, Xuan; Matsubae, Kazuyo
Abstract: This study describes an integrative approach to product flow analysis of (waste) electrical and electronic equipment using trade statistics and consumer survey data. We demonstrate this approach with a case study of mobile phones. Using statistical and empirical data for Australia over 1997–2014, we have shown how different sources of information can be collated and cross-checked to estimate the product in-use stocks and flows, product lifespan and lifespan structure, as well as to detail the product age structure in stock and at the end of life. From our results, the total number of mobile phones in in-use stocks in Australia has been estimated at 46 million at the end of 2014, or about 2 phones per capita. The proportion of phones kept in storage (not being in use) has been constantly rising, reaching 50% in 2012–2014. The average expected lifespan for a mobile phone sold in Australia decreased from about six years in the late 1990s to about five years in the early 2000s, and then stabilised at around four years (±0.5 years). The average time of active use for mobile phones was estimated in the range of 2.0–2.6 years (which includes first use and reuse). The estimated lifespan profile for mobile phones in Australia has been confirmed to be relatively similar to that reported in Japan. While this methodology presented here provided meaningful results, the accuracy and relevance would be improved by better quality of original data. Therefore, in conclusion, we also highlight potential improvements in consumer surveys that would help to enhance the analysis.